Use of donor human milk in nonhospitalized infants: An infant growth study. Issue 2 (6th January 2021) - Bramer, Solange; Boyle, Robert; Weaver, Gillian; Shenker, Natalie
Abstract: When mother's own milk (MOM) is unavailable or insufficient, donor human milk (DHM) is recommended as the next best alternative for low birthweight infants. DHM use for healthy, term infants is increasing, but evidence for growth and tolerability is limited. This retrospective study evaluated growth in term infants in the community who received DHM from a UK milk bank. Mothers of infants receiving DHM between 2017 and 2019 were contacted ( n = 49), and 31 (63.2%) agreed to participate. Fourteen infants received DHM as a supplement to other feeds (MOM and/or infant formula) and 17 were exclusively fed DHM where breastfeeding was impossible (range: 3–6 weeks). Growth was assessed by deriving z ‐scores using the WHO standard for infant growth and compared with 200 exclusively breastfed infants. Multivariate regression analysis revealed no feeding method‐specific association between z ‐score and age, nor between weight and age, suggesting that z ‐scores and growth velocity were not affected by feeding exclusive MOM, supplemental DHM or exclusive DHM. DHM was well‐tolerated with no adverse events that led to early cessation. After receiving supplemental DHM group, 63% of infants whose mothers had no physical barrier to breastfeeding (5/8 infants) were exclusively breastfed. This novel study reports adequate growth outcomes of healthy nonhospitalized infants receiving DHM, either as the sole milk source or supplement. Prospective studies are needed to confirm whether DHM is a suitable feeding alternative for term infants in the community, optimal durations, as well as the impact of DHM availability on breastfeeding rates and maternal mental health. Abstract : DHM recipients were compared with the who infant growth standard (World Health Organization, 2020) by deriving z ‐scores. The WHO Anthro Macro (World Health Organization, 2011 ) was used to calculate weight‐for‐age, length‐for‐age and head circumference‐for‐age z ‐scores; z ‐scores are the standard deviation of an infant's anthropometric measurements when compared with the WHO standard for infant growth and are gender and age specific.